2018
DOI: 10.3892/mmr.2018.8674
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of berberine agonist against impairment of learning and memory skills in severe traumatic brain injury via Sirt1/p38 MAPK expression

Abstract: Berberine has multiple clinical applications, including the treatment of tumors, diabetes, cardiovascular diseases, hyperlipidemia, inflammation, bacterial and viral infections, cerebral ischemic injuries, mental diseases, Alzheimer's disease and osteoporosis. In the present study, the neuroprotective effect of berberine agonist rescue learning and memory in severe traumatic brain injury (TBI), and the possible mechanism underlying these observations was explored. The protective effect of berberine agonist sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 24 publications
3
10
0
Order By: Relevance
“…Besides, several studies have demonstrated that natural compounds protect against TBI by activation of SIRT1. For example, berberine has reported the neuroprotective effect in a severe TBI mouse model by inhibition of the p38 MAPK pathway through the activation of SIRT1 [ 144 ]. Polydatin derived from Polygonum cuspidatum ameliorated the damage of TBI through SIRT1-mediated improvement of endoplasmic reticulum stress and mitochondrial injury [ 145 ].…”
Section: Sirt1 and Cns Diseasesmentioning
confidence: 99%
“…Besides, several studies have demonstrated that natural compounds protect against TBI by activation of SIRT1. For example, berberine has reported the neuroprotective effect in a severe TBI mouse model by inhibition of the p38 MAPK pathway through the activation of SIRT1 [ 144 ]. Polydatin derived from Polygonum cuspidatum ameliorated the damage of TBI through SIRT1-mediated improvement of endoplasmic reticulum stress and mitochondrial injury [ 145 ].…”
Section: Sirt1 and Cns Diseasesmentioning
confidence: 99%
“…[29]. Recent studies have discovered BBR's effect on the other signaling pathways, such as PI3K-Akt, p38MAPK and AMPK signaling etc., in brain disorder [30][31][32], showing the complex mechanism of BBR neuroprotective effect. The anti-depression and anti-anxiety effects are newly identified pharmacological activities of BBR against neuropsychiatric disorders [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“… 5 The emerging evidence suggests that berberine plays an important neuroprotective effect on mice with severe traumatic brain injury by reducing impairment of learning and memory skill. 6 Additionally, berberine is found to ameliorate Aβ pathology and tau phosphorylation in vitro and in vivo and decrease cognitive impairment in AD mouse model. 7 However, the underlying mechanism allows the neuroprotective role of berberine in AD remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%